HUBUNGAN SERVICE RECOVERY DENGAN MINAT BELI ULANG PADA KONSUMEN ANAK-ANAK (STUDI KASUS PADA BEBERAPA OUTLET McDONALD S DI KOTA BANDUNG) - Nina Septina (Bina Ekonomi, 2003)
Recently, the kids had have treated specially as a cluster of potential buyer. One of a number companies which is smartly targeted kids as their customer is McDonalds. Service failure, which occurs on delivering the product, could make consumer dissatisfied, and then will decrease their intention to re-purchase. The goal of this research is to find relation between service recovery and intention to re-purchase on kids customer at McDonalds. Data collected by interviewing 147 respondent. This research find out that the effort on service recovery had succeed on decrease dissatisfied that feel by kid customer, even more, it increase kids intention to re-purchase. The benefit of service recovery is higher than the cost spending in recovery effort. Based on that researcher recommend to keep on giving the recovery in a service if a failure occur.